SO054ONE-YEAR EFFICACY AND SAFETY OF THE LONG ACTING C5 INHIBITOR RAVULIZUMAB FOR THE TREATMENT OF ATYPICAL HAEMOLYTIC URAEMIC SYNDROME (AHUS) IN ADULTS. (6th June 2020) - Barbour, Thomas; Scully, Marie; Ariceta, Gema; Cataland, Spero; Garlo, Katherine; Heyne, Nils; Miyakawa, Yoshitaka; Vallee, Marc; Luque, Yosu; Yoon, Sung-Soo; Menne, Jan; Kavanagh, David
Abstract: Background and Aims: Ravulizumab is a long-acting C5 inhibitor, derived from eculizumab, that is dosed every 8 weeks. Ravulizumab was approved in the United States for patients with atypical haemolytic uraemic syndrome (aHUS) and it is currently under evaluation in the EU based on the phase 3 trial (NCT02949128) efficacy and safety results at 26 weeks in patients with aHUS. Here, we report longer term efficacy and safety of ravulizumab obtained from the trial during the ongoing extension period. Method: This phase 3 trial was a single arm, global, open label study in adults (≥18 years of age) with aHUS naïve to complement-inhibitor therapy. Ravulizumab was administered by intravenous infusion (IV) every 8 weeks during the maintenance phase. Patients fulfilling laboratory criteria for active TMA, ADAMTS13>5%, and negative STEC-HUS testing were eligible. Patients that completed the 26-week initial evaluation period could enter the extension period. The primary endpoint was complete TMA response (normalisation of platelet count and lactate dehydrogenase [LDH], and ≥ 25% improvement in serum creatinine from baseline, measured at 2 separate assessments obtained at least 28 days apart). Secondary endpoints included changes from baseline in haematological parameters, kidney function, and FACIT-fatigue scores. Treatment emergent adverse events were also evaluated. Here, interim cumulative data on primary and secondary endpoints through at least 52 weeks are reported. Results: Forty-seven of 56 enrolled patients completed the initial evaluation period and received at least one dose of ravulizumab in the extension period. All patients achieved complete inhibition of terminal complement as demonstrated by sustained suppression of free-C5 (<0.5 ug/mL). The proportion of patients achieving the individual components of complete TMA response improved during the extension period (Figure). At last follow-up, the number of patients achieving complete TMA response increased from 30/56 (53.6%) in the initial evaluation period to 34/56 (60.7%). Of the four additional patients that reached complete TMA response, three had a previous kidney transplant and one initiated treatment one month after TMA presentation. Improvement in FACIT-fatigue observed in the initial evaluation period was sustained in the extension period. Although three new SAEs were reported during the extension period, there were no further fatal adverse events. As in the primary analysis period, no meningococcal infections occurred through the last patient follow-up. Conclusion: In the extension period of the phase 3 trial, ravulizumab continued to have a good benefit: risk profile. At last follow-up, the cumulative efficacy of ravulizumab to treat complement mediated TMA in patients with aHUS improved to 61% from 54% in the initial evaluation period. Most AEs occurred in the first 26 weeks, and there were no meningococcal infections identified in the study. These results suggest that with ravulizumab further improvement in efficacy is possible with longer treatment with no compromise in safety and improved convenience of 8-week dosing intervals.